GLOBALIST NATIONALISM: A THEORETICAL APPROACH TO THE NATURE OF NATIONALISM IN THE MODERN GLOBAL POLITICAL ECONOMY - Anwar Anaid (European Scientific Journal, ESJ, 2014)
Stressing the evolutionary nature of nationalism and the global market economy, this study explores the possibility of the rise of a nationalism that is adapting to globalization and global integration of the market economy. It suggests rather than weakening nationalism, the modern global political economy is shaping a new form of nationalism: A globalist nationalism that complements the economic policies of globalising states and sub-state nations.